Frailty and the Immune System - Drew William; Wilson Daisy; Sapey Elizabeth (Journal of Aging Research And Healthcare, 2017)
Frailty describes a medical syndrome that confers increased vulnerability to disproportionate changes in health status following minor stressors. With loss of homeostatic reserve in multiple physiological systems, frailty conveys an increased risk of adverse health outcomes. Despite the lack of a clear universal definition, the utilisation of two landmark operational models has allowed a rapid expansion in frailty-centred research. The pathophysiology of frailty is yet to be elucidated in the literature, but a critical role for a heightened inflammatory state is hypothesised. Raised levels of pro-inflammatory cytokines are associated with frailty, with emerging evidence relating their biochemical action with development of the frailty phenotype. Dysregulation of both the innate and adaptive immune system are key components of the frailty syndrome. Remodelling of the T cell compartment and upregulated inflammatory pathways are theorised to propagate the heightened inflammatory state critical in the frailty syndrome. Increased neutrophil counts, in conjunction with ineffective neutrophil migration associated with age, is theorised to produce tissue damage and secondary inflammation conducive of the inflammatory picture in frailty. Beyond the gold standard of the comprehensive geriatric assessment, management of frailty is a fast-evolving area of research. Exercise interventions have shown promising results, improving functional ability and showing beneficial immunomodulation. Vitamin D supplementation, with proposed anti-inflammatory effects, nutritional support and pharmacological treatments all provide promising areas for future therapeutic intervention.
Keywords: Frailty